Towards A Progressive Health Law Paradigm: A Philosophical And Juridical Reconstruction Of The Informed Consent Concept In Indonesia - Hertanto, Yudhi; Purwoto, Ady (JURNAL MAHASISWA YUSTISI, 2026)
The implementation of the informed consent doctrine in Indonesia is frequently trapped in rigid administrative texts and juridical formalism, which consequently overlooks the essence of patient autonomy. The enactment of Law Number 17 of 2023 concerning Health necessitates a conceptual repositioning of medical treatment consent. This study aims to reconstruct the concept of informed consent through the lens of Progressive Law and Bioethics to establish a balance between patient autonomy and legal certainty for medical practitioners. Utilizing a normative juridical research method with statute and conceptual approaches, this study examines the shift from a paternalistic paradigm to an educational-contractual relationship. The findings indicate that legal reconstruction must position informed consent as a continuous ethical communication process rather than a mere signing of a form. While Law No. 17 of 2023 strengthens transparency, it requires the integration of humanitarian values to minimize medical disputes and malpractice cases, which have increasingly appeared in mass media.